Pengendalian Diri Menurut Filsafat Stoikisme (Analisis terhadap Buku Filosofi Teras Karya Henry Manampiring) - Kasma, Cut Puja; Nasution, Hasyimsyah; Faza, Abrar M. Dawud (TSAQOFAH, 2023)
In addition to upsetting one's own peace of mind, the development of concern, envy, fear, regret or bitterness, and excessive pleasure also has an impact on those around one. The value of emotional intelligence and self-control in life because these traits help people understand and regulate their own emotions, and because these traits are more strongly correlated with success and intellect. The purpose of this study is to comprehend the nature of self-control and self-control in light of the Stoic philosophy as it is presented in the book Teras Philosophy. This study employs a qualitative approach and the library research method; it is descriptive in character and frequently employs analysis. The findings of this study suggest that the capacity to manage one's own conduct constitutes the essence of self-control. Stoicism teaches self-control and regulation of one's biological, psychological, and behavioral processes. According to philosophy in the book The Terrace Philosophy, one should be able to employ ratios in all of their responses so that they can live a calm and joyful existence free from unpleasant feelings like sadness, rage, resentment, envy, suspicion, and others. The four virtues are honed through life. Wisdom is the capacity to choose the appropriate course of action in any circumstance, Justice is the fair and honest treatment of others, Courage is the determination to act morally, Restraint, moderation, decency, and self-control over impulses and emotions are all examples of self-discipline.